Was it Worth it? Using Student Loans to Finance a College Degree (Higher Education Politics and Economics, 2020)
This qualitative study explores the perceptions of value added to the lives of graduates who borrowed money to fund their college educations. Through the lens of cognitive dissonance theory, five themes emerged. Overall, the study participants agreed that the ability to take on student loans to fund their education was worth it, but on the other hand feel overburdened with the cost of paying back their loans.  This paper also provides a foundation for future research and identifies public policy shortcomings and suggests solutions.